The Contribution of Teak Dam Ecotourism in Improving the Economic Welfare of the People of Gorang-gareng Village, Nguntoronadi District, Magetan Regency - Fitriani, Hanik (Ascarya: Journal of Islamic Science, Culture, and Social Studies, 2022)
The existence of the river flow in Dam Jati Desa Gorang Gareng Kec. Nguntoronadi Kab. Magetan and its surroundings are considered less productive and this dysfunction becomes anxious and interesting to study.  This research is focused on finding answers to the contributions made by Jati Dam Ecotourism to the level of community welfare. The first problem, what are the forms of Teak Dam tourism, the second statement, how does the Teak Dam Ecotourism Contribution to the level of community welfare, and the third question, what is the strategy of developing Teak Dam ecotourism in improving the welfare of the community?  This study uses a qualitative approach by providing a deep interpretation of the findings in the field based on the facts that occur. Meanwhile, to get the validity of the field data, the procedures used were interviews, observation, and documentation. The data that has been collected is classified and analyzed by examining all data that are finally interpreted.  Based on the data analysis, several findings were generated. First, the forms of ecotourism in Jati Dam include various types of games, entertainment stage, and camping locations. Secondly, the existence of Jati Dam adds to the welfare of the community around Jati Dam, as evidenced by indicators of increasing community income, increasing living standards, higher level of education, better residential homes. Third, the strategy undertaken to develop ecotourism is to form Pokdarwis, the Association of traders, add facilities and tourist facilities, and conduct regular maintenance.